Human capital and personal factors as a determinant of women career success in engineering : A proposed model - Mat, Norazuwa; Mat, Norsiah; Othman, Siti Norezam; Hasnan, Norlena; Razalli, Mohd Rizal; Johari, Husna; Md Isa, Filzah (2008)
Women workforce in Malaysia has increased tremendously. These days, the roles of women are not only restricted to mothers and wives, but they also contribute significantly to the nation development in the labor market. The Malaysian Government has taken steps and actions to recognize women roles and contribution in the development of the country. Nevertheless, the increased participation of female in the workforce does not indicate the job or occupation they hold. Although there is an increment of female engineers in the workforce, their involvement is minimal. There is an existence of gender differences in the profession. Engineering field is perceived as masculine field such as tough, dirty, associate with machinery, which instigates and promoted occupational segregation. Hence, this research intends to explore some relevant issues of women’s career in engineering and proposed a framework for it. This research will randomly select women engineers from all the states in Malaysia. The analysis techniques include descriptive statistics, correlations, hierarchical regression and etc. This research expects to provide some insights on the career development and advancement for women particularly in science and technology; and to provide inputs to policymakers in formulating policies.